If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1n + -7 = -16 Reorder the terms: -7 + -1n = -16 Solving -7 + -1n = -16 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1n = -16 + 7 Combine like terms: -7 + 7 = 0 0 + -1n = -16 + 7 -1n = -16 + 7 Combine like terms: -16 + 7 = -9 -1n = -9 Divide each side by '-1'. n = 9 Simplifying n = 9
| 0=-13b+13b | | 9y^4+12y^2+1=0 | | -13z+13=26 | | -3(4n+6)=-6(n-8) | | .03x+.05(200-x)=9 | | 7m-25=-4 | | 2m+20=26 | | X^2-8x-4=-11 | | 3.3=1.5-0.4 | | x+4k=0 | | -18=x-5 | | -15x+25=-95 | | 9z-17=-35 | | 10y-2=48 | | -11y-9=-86 | | -15p-1=-46 | | 31-3n=4(n+6) | | C+32=-8 | | (5x^3+1)-1=0 | | 3822/14 | | 60.00+42.95p=25.00+49.95p | | -4y-13=15 | | 10x-11=-1 | | -2(n-5)=3n(n-6) | | -13x+15=-63 | | x-.20x=366 | | x-.20x=390 | | 8p-3=77 | | x-20x=390 | | 6(1-4v)=3(4-7v) | | -8x+8x-21=-12-16 | | -y+20=12 |